The New Americans. - Roth, Ronica (Humanities)
Focuses on the television miniseries "The New Americans," which will be aired starting March 2004 as part of the Independent Lens series on Public Broadcasting Service. Theme of the miniseries; Reasons for the migration of the characters to the U.S.; Challenges faced by the immigrants when they arrived in the U.S.